Effects of Information and Communication Technology (ICT) on Students’ Academic Achievement and Retention in Chemistry at Secondary Level (Journal of Education and Educational Development, 2020)
The current paper investigated the effects of information and communication technology on the students’ academic achievement and retention in chemistry. Fifty students of 9th grade were selected randomly from Kohsar Public School and College Latamber Karak. The students were grouped into equivalent groups based on pretest score. In order to collect data, pretest posttest equivalent groups design was used. Mean, standard deviation and independent samples t-test were applied through SPSS for data analysis. Based on statistical analysis, it came to light that information and communication technology positively affects students’ academic achievement and retention and ICT was found more compelling, effective and valuable in teaching of chemistry when contrasted with conventional techniques of teaching. It is recommended that information and communication technology should be used in teaching chemistry for enhancing students’ academic achievement at secondary level.